A CRITICAL REVIEW OF RESILIENCE THEORY AND ITS RELEVANCE FOR SOCIAL WORK - Van Breda, Adrian (Social Work, 2018)
As resilience theory gains traction as a theoretical framework for research in social work, it is important to engage with it critically.This article provides a critical review of resilience theory, drawing on an array of key authors, dating back fifty years. The review addresses three aspects of resilience theory: its definition, the construction of adversity and outcomes, and the nature and scope of resilience processes. The relevance of resilience theory for social work in South Africa is evaluated according to three criteria: the research questions it generates, its contribution to indigenous knowledge and decolonisation, and its contribution to social development.